Ce que commémorer veut dire : la Smithsonian Institution et l’État fédéral à l’approche du Bicentenaire de la Révolution américaine, 1964-1976 - Marie Plassart (Transatlantica)
This article renews the study of national commemorations and public memory that was undertaken in the 1990s through the case study of commemorative practices at the Smithsonian Institution in the years preceding the Bicentennial of the American Revolution (1964-1976). It shows that beyond their heterogeneous forms, commemorative activities share strong common points. The process of preparing for the Bicentennial at the Smithsonian sheds new light on what commemoration is, and pleads for a definition of commemorative activities that is not restricted to their ritual outcome. Commemoration appears to be a collective process of consensus-building, which is framed by the vertical organization of the federal bureaucracy. A top-down commemorative demand pervades the everyday professional activities of actors, who more or less adopt it as their own, depending on their professional status and their places in the chain of command.